STUDY ON THE SITUATION OF THE BOVINES HERDS IN ROMANIA, THE PRODUCTIONS OBTAINED AND THE CONSUMPTION OF MEAT AND DAIRY IN THE PERIOD 2016-2021 - Liviu MARCUTA; Cristiana TINDECHE; Georgiana GURBAN; Silviu Ionut BEIA; Alina MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current work aims to analyze the existing situation in Romania compared to other EU countries, regarding bovines herds, given that this species is one of the ones that causes the highest level of greenhouse gases, with a direct effect on the environment and global warming. This is the reason why the subject has become a priority not only at the community level, but also worldwide. Through the Common Agricultural Policy, important funds have been allocated at the level of the European Union, which will continue to be allocated, not only for the reduction of climate change, but also for the adaptation of the states of the world to these existing climate changes at the global level. Given the path in which animal husbandry influences sustainable development, through the study we have followed both the effective changes, but also the obtained productions, with a direct impact on consumption. It was found that both at the community level, as well as at the national level, there was a decrease in bovines herds in in the period 2016-2020, the reasons being primarily of an economic nature, but equally important being the social and environmental ones. The analysis was carried out starting from the data published by the National Institute of Statistics and Eurostat, data that were then processed and analyzed with the help of statistical methods. Based on these, the conclusions were formulated that show us that in Romania the number of bovines herds decreased by 11% in the period 2016-2021. At the European Union level, Romania ranks 10th in terms of bovines herds and 20th in terms of density/100 ha. Although there are advances in terms of applied technologies or more productive breeds, at the global level the objectives pursued by the reduction of greenhouse gas emissions have not been influenced by these advances, which makes the activity of raising bovines to be considered one with effects negative effects on the environment, but also high consumption of energy and water, which in turn have a negative impact on climate change.